1975
DOI: 10.1071/bt9750435
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Population Levels of Phytophthora cinnamomi in Eucalyptus Forest Soils of Eastern Victoria

Abstract: The behaviour of Phytophthora cinnamomi Rands was examined over a 2 year period on newly cleared and replanted eucalypt sites in the coastal forests of eastern Gippsland, rated as of low, moderate and high die-back hazard in relation to the drainage and disease characteristics of the original forest cover and surrounding trees. The fungus behaved like a saprophytic survivor. Maximum population levels, assessed as a 'population density index' (PDI), occurred within the soil influenced directly by the root mass.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1977
1977
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…The actual numbers of P. cinnamomi propagules in soils reported here can not be compared to other studies because the number of chlamydospores and its distribution in soil can be influenced by differences in soil type, soil pH, soil texture, soil depth, organic matter and bulk densities as well as sampling times among studies (M arks et al. 1975; W este and V ithanage 1978; S hearer and S hea 1987).…”
Section: Discussionmentioning
confidence: 87%
“…The actual numbers of P. cinnamomi propagules in soils reported here can not be compared to other studies because the number of chlamydospores and its distribution in soil can be influenced by differences in soil type, soil pH, soil texture, soil depth, organic matter and bulk densities as well as sampling times among studies (M arks et al. 1975; W este and V ithanage 1978; S hearer and S hea 1987).…”
Section: Discussionmentioning
confidence: 87%
“…At least two other Phytophthora species have been shown to be dispersed by human activities after their initial introduction. Both Weste & Taylor (1971) and Marks et al . (1975) hypothesized that vehicles and logging machinery facilitated the incidence of P. cinnamomi in Australian forests because they observed that host trees infected with the pathogen occurred most commonly along the sides of roads and in recently logged areas.…”
Section: Discussionmentioning
confidence: 91%
“…2005). Humans are also known to play an important role in promoting the occurrence of other invasive Phytophthora species (Weste & Taylor 1971; Marks et al . 1975; Hansen et al .…”
Section: Introductionmentioning
confidence: 99%
“…The treatment regimes we applied were guided by two assumptions: (1) At both sites, the development of well-defined linear disease fronts indicated that autonomous spread of the pathogen was by root-toroot contact (see justification above); and (2) In the absence of host plants, the pathogen is a weakly competitive saprotroph (Marks et al 1975;Malajczuk 1983).…”
Section: Treatmentsmentioning
confidence: 99%